The ATP-Binding Cassette Transporter-2 (ABCA2) Overexpression Modulates Sphingosine Levels and Transcription of the Amyloid Precursor Protein (APP) Gene - Davis, Warren (Current Alzheimer Research, 2015)
The ATP-binding cassette transporter-2 (ABCA2) is a member of a family of multipass transmembrane proteins that use the energy of ATP hydrolysis to transport substrates across membrane bilayers. ABCA2 has also been genetically linked with Alzheimer’s disease but the molecular mechanisms are unknown. In this report, we hypothesized that ABCA2 modulation of sphingolipid metabolism activates a signaling pathway that regulates amyloid precursor protein transcription. We found that ABCA2 overexpression in N2a cells was associated with increased mass of the sphingolipid sphingosine, derived from the catabolism of ceramide. ABCA2 overexpression increased in vitro alkaline and acid ceramidase activity. Sphingosine is a physiological inhibitor of protein kinase C (PKC) activity. Pharmacological inhibition of ceramidase activity or activation PKC activity with 12-myristate 13-acetate (PMA) or diacylglycerol (DAG) decreased endogenous APP mRNA levels in ABCA2 overexpressing cells. Treatment with PMA also decreased the expression of a transfected human APP promoter reporter construct, while treatment with a general PKC inhibitor, GF109203x, increased APP promoter activity. In N2a cells, chromatin immunoprecipitation experiments revealed that a repressive complex forms at the AP-1 site in the human APP promoter, consisting of c-jun, c-jun dimerization protein 2 (JDP2) and HDAC3 and this complex was reduced in ABCA2 overexpressing cells. Activation of the human APP promoter in A2 cells was directed by the upstream stimulatory factors USF-1 and USF-2 that bound to an E-box element in vivo. These findings indicate that ABCA2 overexpression modulates sphingosine levels and regulates transcription of the endogenous APP gene.
Keywords: ABCA2